AL-SIYASAH WA AL-AKHLAQ ‘INDA MACHIAVELLI WA AL-MAWARDI - Fuad Muhammad Zein (IAIN Surakarta, 2016)
The issue of politics and ethics are two sides of a coin that invited attention of medieval scholars both in the West and the Islamic world. Although interrelated, but the implementation raises the difference between the two worlds. For the Western world, represented by Machiavelli, politics and ethics should be separated. A ruler should not be bound by ethics and tradition, and does not need to obey the law. In domestic relations affairs, a ruler must collect on his love and fear of people. While in foreign affairs, a ruler must reflect